Penerapan Budaya Organisasi dalam Peningkatan Pelayanan Administrasi Pendidikan di MAN 2 Bone - Ananda Musli, Firdiana; Arsyad, Arisal (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This thesis discusses the Application of Organizational Culture in Improving Administrative Services at MAN 2 Bone. The purpose of this study is to find out the extent of the application of organizational culture in improving the educational administration process. The type of research used in this study is qualitative research. This research uses a management approach and a sociological approach. In collecting data, observation, interview, and documentation methods are used. As well as using data analysis techniques, namely data reduction, data presentation and conclusion drawn. The results of this study show that there is indeed an organizational culture policy in MAN 2 Bone that has existed for a long time, one of the cultures that is upheld in MAN 2 Bone is the culture of